Retardation of the phase segregation of liquid mixtures with a critical point of miscibility. Issue 11 (26th July 2018) - Califano, Filomena; Mauri, Roberto
Abstract : The phase transition extraction (PTE) process consists of bringing a partially miscible mixture from the single‐phase to the two‐phase region of its phase diagram. Its most important characteristic is that the resulting phase separation is very fast, and hardly affected by coalescence‐retarding impurities. In this work we study two counter‐cases, where the PTE process appears to be severely retarded. First, we consider the ouzo effect, where the mixture forms very stable metastable micro‐emulsions, showing that this process can be generalized, leading to a reverse ouzo effect, where a modifier is added in large quantities. The second retardation technique consists of using very viscous solvents. We found that, in agreement with the predictions of the phase field model, the growth rate of the nuclei during the initial stage of phase separation does not depend on viscosity, while, on the other hand, when the size of the nuclei exceed their capillary length, gravitational effects become relevant and the settling time is proportional to the viscosity of the continuous phase. © 2018 American Institute of Chemical Engineers AIChE J, 64: 4047–4052, 2018